Post hoc analysis of ADAMANT, a phase 2 clinical trial of active tau immunotherapy with AADvac1 in patients with Alzheimer's disease, positive for plasma p-tau217 - Kovacech, Branislav; Cullen, Nicholas C; Novak, Petr; Hanes, Jozef; Kontsekova, Eva; Katina, Stanislav; Parrak, Vojtech; Fresser, Michal; Vanbrabant, Jeroen; Feldman, Howard H; Winblad, Bengt; Stoops, Erik; et al. (Alzheimer's research & therapy, 2024)
BACKGROUND: The spread of tau pathology closely correlates with the disease course and cognitive decline in Alzheimer's disease (AD). Tau-targeting immunotherapies are being developed to stop the spread of tau pathology and thus halt disease progression. In this post hoc analysis of the ADAMANT clinical trial, we examined the performance of AADvac1, an active immunotherapy targeting the microtubule-binding region (MTBR) of tau, in a subgroup of participants with elevated plasma p-tau217, indicating AD-related neuropathological changes. METHODS: ADAMANT was a 24-month, randomized, placebo-controlled, parallel-group, double-blinded, multicenter, phase 2 clinical trial in subjects with mild AD. The trial participants were randomized 3:2 to receive six doses of AADvac1 or placebo at 4-week intervals, followed by five booster doses at 14-week intervals. The primary outcome was safety. The secondary outcomes were the Clinical Dementia Rating-Sum of Boxes (CDR-SB), the Alzheimer's Disease Cooperative Study - Activities of Daily Living score for Mild Cognitive Impairment 18-item version (ADCS-ADL-MCI-18), and immunogenicity. Volumetric MRI, plasma neurofilament light (NfL), and glial fibrillary acidic protein (GFAP) were exploratory outcomes. The inclusion criterion for this post-hoc analysis was a baseline plasma p-tau217 level above the cutoff for AD. RESULTS: Among 196 ADAMANT participants, 137 were positive for plasma p-tau217 (mean age 71.4 years, 59% women). AADvac1 was safe and well tolerated in this subgroup. AADvac1 reduced the rate of accumulation of log-plasma NfL by 56% and that of GFAP by 73%. The treatment differences in the CDR-SB and ADCS-ADL-MCI-18 scores favored AADvac1 but were not statistically significant. AADvac1 had no effect on whole-brain volume but nonsignificantly reduced the loss of brain cortical tissue in several regions. Importantly, the impact on the study outcomes was more pronounced in participants with higher anti-tau antibody levels. CONCLUSIONS: These results suggest that AADvac1 tau immunotherapy can reduce plasma biomarkers of neurodegeneration and neuroinflammation. These findings and possible observations on brain atrophy and cognition are hypothesis-generating and warrant further evaluation in a larger clinical trial. TRIAL REGISTRATION: EudraCT 2015-000630-30 (primary) and NCT02579252.
Keywords: výsledek terapie; Plasma biomarkers; proteiny tau; Male; Glial fibrillary acidic protein (GFAP); biologické markery; Alzheimer’s disease; Biomarkers; testy pro posouzení mentálních funkcí a demence; Alzheimerova nemoc; Alzheimer Disease; Tau; Aged; mužské pohlaví; senioři; Neurofilament light (NfL); Mental Status and Dementia Tests; tau Proteins; AADvac1; dvojitá slepá metoda; Treatment Outcome; Immunotherapy; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; Immunotherapy, Active; Plasma phosphorylated tau 217; aktivní imunoterapie; Double-Blind Method; Female; lidé středního věku; Middle Aged